Safe disposal of Coal Bottom Ash using cement based solidification and stabilization techniques / Sajedeh Sadat Ghazizadeh Hashemi - Sajedeh Sadat , Ghazizadeh Hashemi (2018)
Coal Bottom Ash (CBA) is one of the widely-produced residues of coal incineration in electric power plants. It is categorized as scheduled waste that must be disposed at a licensed treatment plant in the Malaysia. The annual extraction of such a huge amount of waste needs a massive transfer field, which constitutes a threat to the environment. However, the utilization of such residue as a fine aggregate in concrete can be an environmentally-friendly opportunity. Moreover, contaminated heavy metals contained in the CBA such as nickel, copper, cadmium and lead can be immobilized using Solidification/Stabilization technique to reduce toxic solubility and leachability. As observed in this study, CBA has a reactive fraction with pozzolanic characteristics. This provides stronger mortar mixture when a medium volume of the CBA (up to 40%) is substituted with silica sand. The compressive strength value of the specimen using 40% CBA with W/C ratio of 0.55 at 56 days was 55 MPa, which reached the same strength limit of control mortar mixture. However, the reduction of compressive strength in high-volume CBA replacement is attributed to the porous structure of CBA, which causes absorption of the mixing water as well as an increase in the total pore volume of the mortar mixtures. OPC-based immobilization and encapsulation of contaminated heavy metals was effective for prevention of metals leaching, were below the applicable Malaysian Environmental Quality Act and highly decreased to zero leaching, further high enough strength property and acceptable permeable porosity value attained by OPC/CBA ratio of 2 which was more than sufficient to be disposed safely in landfills. Besides, the solidified/stabilized samples exhibited ettringite and amorphous C-S-H. Inclusion of CBA has changed the surface of the solidified sample into more C-S-H and less ettringite. The main crystal in the solidified samples was calcite, which were formed by carbonation reaction of C-S-H and C-H with CO2 in the cement hydration product. Thermogravimetry analysis of solidified samples exhibited the active pozzolanic reaction at temperature of 400 to 750 ˚C, shown by the weight loss of Ca(OH)2 and decomposition of carbonation product. The optimum mixture of 40% CBA replacement at constant W/C ratio of 0.55 achieved applicable value in terms of compressive strength, abrasion resistance and water absorption to fabricate Portland cement paving blocks. Moreover, it is observed that the degree of shrinkage of CBA/ silica sand paving blocks decreased with increase in the CBA content. This reduction might be attributed to pore texture of the CBA that also resulted in reducing compressive strength.